2023
DOI: 10.1111/his.14850
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and molecular features of indolent natural killer‐cell lymphoproliferative disorder of the gastrointestinal tract

Abstract: Clinicopathological and molecular features of indolent natural killer-cell lymphoproliferative disorder of the gastrointestinal tractAims: Indolent natural killer (NK) cell lymphoproliferative disorder of the gastrointestinal (GI) tract (iNKLPD) is a rare, recently recognised neoplasm. Most of the reported tumours are confined to the GI tract, while a small subset of the tumours harbour JAK3 mutations. We collected four cases of iNKLPD with the goal of adding additional information to the current knowledge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Nevertheless, studies have identified JAK3 K563_C565del mutations in 30% of patients with NKCE. 17,21 However, JAK3 mutations have also been observed in various types of T-and NK-cell lymphomas, indicating that they are not specific to the NKCE process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, studies have identified JAK3 K563_C565del mutations in 30% of patients with NKCE. 17,21 However, JAK3 mutations have also been observed in various types of T-and NK-cell lymphomas, indicating that they are not specific to the NKCE process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the clonality of NK cells makes it difficult to determine whether NKCE represents reactive or neoplastic growth. Nevertheless, studies have identified JAK3 K563_C565del mutations in 30% of patients with NKCE 17,21 . However, JAK3 mutations have also been observed in various types of T‐ and NK‐cell lymphomas, indicating that they are not specific to the NKCE process.…”
Section: Discussionmentioning
confidence: 99%
“…Both systems recognized indolent NK-cell lymphoproliferative disorder, which is newly added to both classification systems and replaces the term NK-cell enteropathy and lymphomatoid gastropathy [33,34]. Recent mutational studies have provided evidence that this is indeed a neoplasm associated with recurrent mutations in JAK3 [35,36].…”
Section: Indolent Gastrointestinal T-/nk-cell Neoplasmsmentioning
confidence: 99%